KONSTRUKSI MUTAN PROTEIN FOSFATASE ptc2D Saccharomyces cerevisiae DENGAN METODE PENGGANTIAN GEN TARGET DENGAN POLYMERASE CHAIN REACTION (PCR) - Hermansyah Hermansyah (Molekul, 2011)
Yeast Saccharomyces cerevisiae is an excellent model to studi genes function of eukarotic cells such as study of gene encoding protein phosphatase PTC2. Novel phenotypic caused by mutated gene is an important step to study function of gene. In this study constructed mutant of PTC2 gene encoding protein phosphatase. Method that used in this construction was replacement of target gene (PTC2) with auxotroph marker Candida albicans HIS3 by Polymer Chain Reaction (PCR) or called by PCR-mediated disruption. Mutant colonies which grew in selective medium SC without histidine were confirmed by PCR amplification. By using 1% Agarose gel electrophoresis the result showed that size of ptc2D::CgHIS3 transformant was 3.52 kb while wild type strain was 2.9 kb, indicated thatptc2D::CgHIS3 has integrated on chromosome V replacing PTC2 wild type.